CHEMICAL SPECIATION APPROACH IN THE RISK EVALUATION OF ENVIRONMENTAL DISASTER CONTAMINANTS EXPOSURE - Dwindrata Aviantara (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
Heavy metals are common environmental contaminants. Depending on the amount and chemical species that present, these heavy metals can turn into environmental pollutants which in certain environmental conditions can be in a biologically available form so that they have the potential to cause toxic effects. Analysis of the risk of heavy metal exposure by relying on the total amount of heavy metals does not provide a real picture of the relationship between exposure and toxicity. A chemical speciation approach that takes into account the chemical state of heavy metal species with potential for mobility, bioavailability and toxicity is a more rigorous strategy in risk analysis of heavy metal exposure. This is because the large total amount of heavy metals is not necessarily able to provide the metal in a biologically available form. On the other hand, the total amount of heavy metals which is considered safe because it does not exceed the regulatory quality standards, but chronic exposure to the forms of chemical species that are biologically available actually poses a threat in the long term. With the support of reliable laboratory equipments and accurate computational chemical speciation modeling, the heavy metal chemical speciation approach is the right tool in environmental pollution risk analysis.